1999
DOI: 10.1590/s0066-782x1999000700002
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease, microalbuminuria and lipid profile in patients with non-insulin dependent diabetes mellitus

Abstract: Diabetes mellitus is an important factor associated with increased cardiovascular morbidity and mortality, due to coronary artery disease (CAD), stroke and peripheral vascular disease. Age adjusted coronary artery disease prevalence in diabetic patients, in the United States, is between 30 and 51%; peripheral vascular disease and stroke prevalences are 9 and 10%, respectively 1 . Recently, a study in Brazil reported a 2.3 greater in-hospital mortality rate in diabetic compared with nondiabetic patients, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(51 reference statements)
0
2
0
2
Order By: Relevance
“…Thus, prospective clinical assays with correction of postprandial hyperglycemia will be able to characterize the actual role of this control in the prevention of cardiovascular events. Notably, the presence of multiple associated risk factors in diabetic patients presupposes an intensive therapeutic intervention in these patients 39 .…”
Section: Postprandial Hyperglycemia and Cardiovascular Morbi-mortalitymentioning
confidence: 99%
“…Thus, prospective clinical assays with correction of postprandial hyperglycemia will be able to characterize the actual role of this control in the prevention of cardiovascular events. Notably, the presence of multiple associated risk factors in diabetic patients presupposes an intensive therapeutic intervention in these patients 39 .…”
Section: Postprandial Hyperglycemia and Cardiovascular Morbi-mortalitymentioning
confidence: 99%
“…Another study found that cholesterol and triglyceride levels were elevated in 28 treadmill positive cases compared to 15 treadmill negative cases (p<0.01). 20 This study showed that significantly higher mean duration of diabetes (8.87 years) in TMT positive cases, in which 21.31%, 33.33%, 70% & 75% cases are of ≤5 years, 6-10 years, 11-15 years and 16-20 years of diabetes; respectively, suggestive that higher incidence of asymptomatic ischemic heart disease with prolong duration of diabetes. Above 10 years of duration of diabetes has 2 fold risk of developing asymptomatic ischemic heart disease in diabetic patients.…”
Section: Discussionmentioning
confidence: 54%
“…No entanto, consideramos que esse dado não acrescentaria informações relevantes, uma vez que qualquer paciente diabético tem uma pontuação maior no escore de Framingham do que o não-diabético (dois pontos para os homens e quatro para as mulheres diabéticas, versus zero para não-diabéticos). Além disso, a população diabética tem maior prevalência de HAS e dislipidemia, como já demonstrado em vários estudos (29)(30)(31), incluindo dados de nosso meio (32).…”
Section: Discussionunclassified